2011
DOI: 10.1177/0886260511430388
|View full text |Cite
|
Sign up to set email alerts
|

Examining Self-Protection Measures Guarding Adult Protective Services Social Workers Against Compassion Fatigue

Abstract: Little research has focused on the risk factors, effects, and experiences of compassion fatigue among gerontological social workers. This qualitative study explores the experiences and perspectives of nine Adult Protective Services (APS) social workers in relation to compassion fatigue. Results show that the APS social workers combined personal characteristics and professional factors to develop boundary-setting mechanisms that protected them from experiencing the deleterious symptoms and effects of compassion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, due to the nature of their work, adult/elder protective service and child protective service workers are at-risk for experiencing various negative psychological effects (e.g. compassion fatigue or STS; Bourassa, 2012;Kim, 2011). Therefore, the current study examined the rates of VT, STS, and burnout in adult/elder protective service and child protective service workers, specifically assessing the effect of PIL on these outcomes, irrespective of hours worked per week, ethnicity, and participants' years of experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the nature of their work, adult/elder protective service and child protective service workers are at-risk for experiencing various negative psychological effects (e.g. compassion fatigue or STS; Bourassa, 2012;Kim, 2011). Therefore, the current study examined the rates of VT, STS, and burnout in adult/elder protective service and child protective service workers, specifically assessing the effect of PIL on these outcomes, irrespective of hours worked per week, ethnicity, and participants' years of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interventions to reduce these negative effects in social workers should be implemented; yet, numerous interventions (e.g. "thought engagement" or crisis debriefing, Bourassa, 2012;Pulido & Lacina, 2010, respectively) have found few long-term benefits (Pulido & Lacina, 2010) or have not yet been adapted for use with adult/elder protective service workers. Additionally, there have been protective factors (e.g.…”
Section: Common Psychological Responses For Protective Service Workersmentioning
confidence: 99%
“…Based on Figley's (1995) research, "Compassion fatigue can be manifested in the physiological, psychological, spiritual, and emotional issues that people who have posttraumatic stress disorder also experience" (as cited in Bourassa, 2012Bourassa, , p. 1700. Though the compassion-fatigued caregiver is not directly experiencing a primary traumatic event, he or she is constantly being exposed to the trauma and stress of others in his or her caregiver role, thereby experiencing what some call secondary traumatic stress.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…These implications were reminiscent of a phenomenon described in the literature as compassion fatigue (Adams, Boscarino, & Figley, 2006;Austin, Goble, Leier, & Byrne, 2009;Bourassa, 2012;Figley, 2002;Najjar, Davis, Beck-Coon, & Carney Doebbeling, 2009). Studies on family violence and sexual abuse showed that following repeated exposure to traumatic content over time and the empathic relationship that developed during the therapeutic process, social service professionals might experience emotional fatigue related to compassion toward their clients' suffering.…”
Section: Discussionmentioning
confidence: 83%